On the asymptotics of laguerre matrix polynomials - Sastre J.; Jódar L. (Utilitas Mathematica, 2006)
This paper deals with the asymptotics of normalized Laguerre matrix polynomials of a complex matrix parameter in the positive real line. Asymptotic expressions of Laguerre matrix polynomials expressed in terms of trigonometric matrix functions are proposed.